Changes in heterosis via intra and interpopulation selection - Júnior, Cláudio Lopes de Souza; Filho, José Branco de Miranda (Pesquisa Agropecuaria Brasileira, 2014)
In view of the lack of consistency of empirical results on changes in heterosis through intra and interpopulation selection, the objective of the present work was to study, theoretically, the expected changes in heterosis as a result of those two selection schemes. For that purpose, expressions were obtained in order to explain the changes in gene frequencies through interpopulation selection and changes in heterosis (Δh), as a function of gene frequencies and genotypic e effect, according to Falconer's model. It was demonstrated that Δh ≅ 2(p - r) d(Δp - Δr); also for several combinations of gene frequencies (p and r) of both populations it was showed that Δh has a negative trend for intrapopulation selection and a positive trend for interpopulation selection, for models with either complete dominance or overdominance.